Bioinspired materials and membranes for energy-efficient liquid separation - Chen, Ting (The University of Edinburgh, 2021)
Liquid separations play a significant role in a wide range of industrial applications, including water purification, food and pharmaceutical industries. Membrane separation has been proved to be promising for liquid separations due to its high efficiency, low operation cost and energy-saving performance. Despite progress in recent decades, the development of advanced materials and membranes for energy-efficient liquid separations is highly desired. Fortunately, nature provides a rich source of inspiration for fresh ideas in smart materials design. This work focuses on the design of films, nanomaterials, and membranes with bioinspired superwetting surface properties or nacre-like lamellar structures for energy-efficient liquid separations, including oil/water separation and molecular separation. Bioinspired materials with superwetting surfaces have attracted widespread interest, particularly for liquid separations. Although considerable progress has been made in the past decade, it is still challenging to scale up the application of bioinspired materials in liquid separations. This is because the majority of existing bioinspired materials are either expensive to fabricate or involve energy-intensive, and/or time-consuming production processes. In this work, energy-effective and time-saving methods were explored to develop bioinspired materials. Zeolitic imidazolate frameworks (ZIFs), were employed as major building blocks for the bioinspired materials and membranes design. Applications of the prepared bioinspired materials in oil/water separation and molecular separation in organic solvents were systematically investigated. Inspired by superwetting surfaces in nature, mesh films with switchable superwettability were fabricated using two dimensional ZIF-L nanoplates. The preparation process was completed within 2 hours through a rapid seeding and secondary growth process under ambient conditions. The ZIF-L mesh films exhibited in-air superamphiphilic, underwater superoleophobic and underoil superhydrophobic properties, and showed outstanding performance in solely-gravity-driven oil/water mixture separation. A prewetting-induced switchable permeation function was found for the hierarchical ZIF-L surface, achieving both “oil-blocking” and “water-blocking” separation. Chemical stability is one of the most important factors affecting the long-term applications of ZIFs based materials in liquid separations. To enhance the chemical stability of ZIFs, a novel oil/water interfacial assembly strategy was developed to prepare oleic acid (OA) decorated ZIFs, which was denoted as ZIF−OAs. The prepared ZIF−OAs exhibited bioinspired superhydrophobic surface properties and showed exceptional water stability and chemical stability. Furthermore, a simple sequential drop-casting method was developed to coat as-synthesized ZIF−OAs onto porous membrane surfaces. The molecular separation performances of the prepared ZIF−OAs coated membranes were explored. Another important aspect considered in this work for realizing energy-efficient liquid separation is enhancing the permeation rate of the membrane materials. Membranes with ultrafast solvent transport rates can largely reduce the energy consumption in the separation processes. To enhance the membrane permeability, graphene oxide (GO)/ZIF-8 composite membranes with ultrafast diffusion nanochannels were developed. ZIF-8 nanocrystals were intercalated in the GO interlayers via in situ self-assembly using a facile vacuum-assisted filtration method. The obtained GO/ZIF-8 membranes showed a nacre-like lamellar structure and exhibited well-defined nanochannels with ultrafast solvent transport. Moreover, these membranes provided selective molecular separation performance for various binary dye mixtures with high separation efficiencies. The results presented in this thesis make a valuable contribution to promoting the facile preparation of bioinspired materials and membranes. The fabrication strategies developed in this work are time-saving and energy-effective, thus are beneficial for the mass production of bioinspired materials at a large scale. In addition, this work could also contribute to promoting the practical applications of bioinspired materials and membranes in liquid separations. The smart superwetting surface properties, exceptional chemical stability, and superior permeability enable the materials and membranes to realize energy-efficient oil/water separation and molecular separation with long-term stability.
Keywords: Bioinspired; membrane; liquid separation; MOF